Demographic Characteristics as Predictors of Medicine and Health Services Access Difficulties and Economic Problems during Covid 19 in Java, Indonesia - Cati Martiyana; Leny Latifah; Yusi Dwi Nurcahyani; Diah Yunitawati; Marizka Khairunnisa1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. The very rapid spread of COVID-19 infection, causing large-scale social restriction in manyparts of the world. A lot of businesses and working places closed. Health services and medicine were in highdemand. Objective. This study aims to determine the demographic characteristics that predict medicineand health services access difficulties and economic problems. Method. This was cross-sectional researchconducted in Java, Indonesia. The research sample was 1,385 individuals aged 15 years and over who livedin Java and had filled out a survey via a google form. Data analysis using multivariate logistic regression.Results. The risk of difficulty accessing medicine and health services and economic difficulties was higherfor males, had income < 3 million per month, and do not have health insurance. Conclusion. Male, hadlow income, and do not have health insurance are at higher risk for having difficulty accessing medicines/health services and experiencing economic difficulties. Meanwhile, respondents under 25 years of age havea higher risk of experiencing difficulties in accessing medicines and health services. The government needsto implement a strategy to reduce health and economic problems due to COVID-19 and pay attention toindividuals under 25 years of age to access health services/medicines.